Sustainable production of high purity curcuminoids from Curcuma longa by magnetic nanoparticles: A case study in Brazil - Ferreira, Maria Izabela [UNESP]; Magro, Massimiliano; Ming, Lin Chau [UNESP]; da Silva, Monica Bartira [UNESP]; Ormond Sobreira Rodrigues, Luan Fernando [UNESP]; Zanoni do Prado, Débora [UNESP]; Bonaiuto, Emanuela; Baratella, Davide; De Almeida Roger, Jessica; Pace Pereira Lima, Giuseppina [UNESP]; Rossetto, Monica; Zennaro, Lucio; et al. (Elsevier, 2017)
Large volumes of residual biomass could represent a matter of concern for large-scale purification of natural compounds, heavily influencing processing industries and logistic sizing, amount of solvents employed for the extraction processes and the final chemical and biological waste generation. In the present study, carried out in Brazil, the production of curcuminoids in Curcuma longa L. rhizomes was maximized as a function of plant maturity and solar UV exclusion. Noteworthy, curcuminoid content reached its maximum at around the end of the early vegetative phase (65 days after planting), henceforward plant growth determined only a detrimental accumulation of wastes. The harvesting at this early phase of plant maturation led to a more than tenfold reduction of exceeding biomass. In addition, by means of an innovative, sustainable and high efficient magnetic purification process for curcuminoids based on Surface Active Maghemite Nanoparticles (SAMNs), an outstanding yield of 90% and >98% purity, were achieved in a single magnetic purification step. The formation of the SAMN-curcuminoid complex (SAMN@curcuminoid) was demonstrated by optical and electron spin resonance spectroscopy and electron microscopy. The scalability of the purification method was proved by the application of an automatic modular pilot system for continuous magnetic purification of curcuminoids, capable of managing 100 L day−1 of SAMN@curcuminoid suspensions. The presented multidisciplinary approach embodies the fundamental principles of cleaner production providing a paradigm for the utilization of magnetic nanoparticles for biomolecule purification. Moreover, Brazilian agro-industries can benefit from sustainable innovation strategy outlined by the current study.
Keywords: Biomass reduction; Curcumin production; Curcumin purification; Magnetic nanoparticles; Magnetic purification; Turmeric